Elimination of 15N-thymidine after oral administration in human infants. - Niyatie Ammanamanchi; Jessie Yester; Anita P Bargaje; Dawn Thomas; Kathryn C Little; Shannon Janzef; Kimberly Francis; Jacqueline Weinberg; Jennifer Johnson; Thomas Seery; Tyler Hutchinson Harris; Bryan J Funari; et al. (PLoS ONE)
Background We have developed a new clinical research approach for the quantification of cellular proliferation in human infants to address unanswered questions about tissue renewal and regeneration. The approach consists of oral 15N-thymidine administration to label cells in S-phase, followed by Multi-isotope Imaging Mass Spectrometry for detection of the incorporated label in cell nuclei. To establish the approach, we performed an observational study to examine uptake and elimination of 15N-thymidine. We compared at-home label administration with in-hospital administration in infants with tetralogy of Fallot, a form of congenital heart disease, and infants with heart failure. Methods We examined urine samples from 18 infants who received 15N-thymidine (50 mg/kg body weight) by mouth for five consecutive days. We used Isotope Ratio Mass Spectrometry to determine enrichment of 15N relative to 14N (%) in urine. Results/findings 15N-thymidine dose administration produced periodic rises of 15N enrichment in urine. Infants with tetralogy of Fallot had a 3.2-fold increase and infants with heart failure had a 4.3-fold increase in mean peak 15N enrichment over baseline. The mean 15N enrichment was not statistically different between the two patient populations (p = 0.103). The time to peak 15N enrichment in tetralogy of Fallot infants was 6.3 ± 1 hr and in infants with heart failure 7.5 ± 2 hr (mean ± SEM). The duration of significant 15N enrichment after a dose was 18.5 ± 1.7 hr in tetralogy of Fallot and in heart failure 18.2 ± 1.8 hr (mean ± SEM). The time to peak enrichment and duration of enrichment were also not statistically different (p = 0.617 and p = 0.887). Conclusions The presented results support two conclusions of significance for future applications: (1) Demonstration that 15N-thymidine label administration at home is equivalent to in-hospital administration. (2) Two different types of heart disease show no differences in 15N-thymidine absorption and elimination. This enables the comparative analysis of cellular proliferation between different types of heart disease.